PENGARUH PENAMBAHAN BERBAGAI STARTER PADA SILASE RANSUM BERBASIS LIMBAH PERTANIAN TERHADAP PROTEIN KASAR, BAHAN KERING, BAHAN ORGANIK, DAN KADAR ABU - Dimas Cahyo Kuncoro; Muhtarudin ,; Farida Fathul (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The purpose of this study was to determine the effect of adding a starter in the making of silage. This study was compiled using completely randomized design with 4 treatments and 3 replications. The treatment in this study is R0 : basal ration, R1 :basal ration + (EM-4 4%), R2 : basal ration + EM-4 who bred 4%, R3 : basal ration + rumen fluid 4%. The result showed the addition of treatment on trial the addition of 4% starter EM-4, EM-4 who bred and rumen fluid very significant effect in the levels of dry matter and organic matter as well as the real impact on the levels of crude protein and ash content. Best silage, silage contained in the basal ration (R0). Keywords: Em-4, Em-4 bred, rumen fluid, chemical quality, silage.